Psychosocial Impact of Recurrent Pregnancy Loss in a G7P0A6 Patient with Hyperthyroidism: A Case Report - Leonardus Yogie Ricardo; Hartati; Kemala Andini Prizara; Sisca Yulistiana (Sriwijaya Journal of Medicine, 2026)
Recurrent pregnancy loss presents significant physical and psychosocial challenges, especially when complicated by comorbidities such as Graves’ disease and polycystic ovary syndrome (PCO) with suspected insulin resistance. This case involves a G7P0A6 woman at 21 weeks’ gestation with euthyroid-phase Graves’ disease and PCO, expressing a desire for tubectomy if another miscarriage occurs. She has no living children and shows psychosocial distress related to previous losses. Termination at 21 weeks carries risks of hemorrhage, infection, and endocrine instability, particularly in patients with autoimmune and metabolic disorders. Continuing the pregnancy, however, also entails potential complications including endocrine imbalance, fetal growth restriction, preterm delivery, or intrauterine death. Psychologically, repeated miscarriage can provoke anxiety, guilt, and depressive symptoms, often influencing irreversible decisions like sterilization without full consideration of alternatives. Given her emotional vulnerability and absence of living offspring, permanent contraception should be deferred. A multidisciplinary approach—integrating obstetrics, internal medicine, psychiatry, and psychology—is essential to optimize maternal health and guide ethical decision-making. Continuing the pregnancy with close medical and psychological monitoring is preferable to termination, as both options carry comparable risks, but continuation preserves the possibility of a living child. Antenatal psychological support and comprehensive contraceptive counseling should be provided to help the patient make well-informed, emotionally balanced decisions regarding future fertility.